REHABILITATION EXERCISES AND THEIR EFFECT ON THE STRENGTH OF THE ELECTRICAL STIMULATION DEVICE FOR THE THIGH MUSCLES FOR FEMALE BASKETBALL PLAYERS - Assistant Prof. Suhad Ibrahim Hamdan (Scholars Digest Publishing, 2025)
Exercise is a selected group of exercises given to strengthen specific muscles in the body to carry out its full function. It is based on physiological, anatomical and mechanical principles depending on the diagnosis of the condition and the physical examination of each individual individually, and it includes various exercises The research aimed to identify the effect of exercise exercises accompanied by an electrical stimulation device on the strength and electrical activity of the thigh muscles for female basketball players. The researcher assumed that the prepared exercises have a positive effect in developing the strength and electrical activity of the thigh muscles for the research sample. The experimental method was chosen because it is appropriate for the research procedures. The research sample consisted of 12 female players representing the Al-Mustansiriya University basketball team. Appropriate tests and measurements were conducted, including physical tests such as strength and force endurance, and physiological variables, which include electrical activity. After collecting and transcribing the data, the researcher discussed the results and reached a number of results, the most important of which are: that exercise has a positive effect in developing the strength, endurance, and electrical activity of the thigh muscles for the players in the research sample. The researcher recommended the necessity of using exercises to accompany the electrical activity of the players in order to develop strength, endurance, and electrical activity. For the thigh muscles and thus obtaining good results for female players.
Keywords: Rehabilitative exercises, basketball, electrical stimulation device.